Cepstral peak prominence in normophonic adults: the effect of gender and speech task segmental composition - Yanushevskaya, Irena (My University, 2023)
Cepstral Peak Prominence (CPP) is currently recommended for clinical use by speech and language therapists as an objective and robust measure of dysphonia. Its widespread use in clinic is stalled, however, by the relative conceptual complexity of CPP and by the lack of baseline normative data. This paper describes CPP values extracted from the audio recordings of normophonic adults 25-55 years old living in Ireland. Audio data was collected remotely, using mobile phones, from 42 participants (21 female). Speech tasks included sustained vowels as well as sentences with different segmental composition (vowels and approximants, nasals, voiced and voiceless obstruents). CPP values were extracted using Praat. We describe the effects of gender, speech task segmental composition and CPP extraction method (with and without voice activity detection) on the obtained CPP values. The results may serve as a normative baseline for clinical voice analysis and assessment in speech and language therapy practice.
ICPhS
Keywords: Cepstral Peak Prominence, normative data, gender, speech task, clinical voice analysis